Uji Aktivitas Antibakteri Ekstrak Etanol Tanaman Yodium (Jatropha Multifida L.) Terhadap Bakteri Staphylococcus Aureus Atcc 6538 Dan Escherichia Coli Atcc 11229 Secara Invitro - Sansetyawati, Meiliyana Silvi; , dr. M. Amin Romas, DSMK; , dr. Devi Usdiana Rosyidah, M.Sc (2015)
Background: The iodine plant (Jatropha multifida L) contains alkaloid, tanin, flavonoid and saponin are presumably able to inhibit bacteria growth so that the ethanol extract of iodine plant indicated having an antibacterial activity. Objective: To understand antibacterial activity of the iodine plant ethanol extract antibacterial against Staphylococcus aureus and Escherichia coli in vitro. Methods: This study used laboratory experimental research design (laboratories experiment) with posttest only control group design method. The subject of the research was iodine plant ethanol extract. Extract would be tested with antibacterial activity against Staphylococcus aureus ATCC 6538 and Escherichia coli ATCC 11229 using wells method with a concentration of 5% b/v, 10% b/v, 20% b/v, 40% b/v, 60% b/v and 80% b/v. To analyze the data used Kruskal-Wallis non Parametric and Mann-Whitney test. Result: The iodine plant ethanol extract has antibacterial activity against Staphylococcus aureus at concentration of 40% b/v, 60% b/v and 80% b/v each with an inhibition zone diameter of 8 mm, 9,4 mm and 12 mm. Statistically it has significant antibacterial power with p = 0,000 (p < 005) but less effective compared with positive control. While Escherichia coli has no antibacterial effect at all concentration. Conclusion: The iodine plant ethanol extract has antibacterial activity against Staphylococcus aureus ATCC 6538 at concentration 40% b/v, 60% b/v and 80% b/v but not effective against the bacteria Escherichia coli ATCC 11229 in vitro.